Prevalence and outcomes of laser treatment of aggressive posterior retinopathy of prematurity. (23rd January 2014) - Gunn, David J; Cartwright, David W; Gole, Glen A
Abstract Background To describe outcomes in a cohort of extremely premature infants treated for aggressive posterior retinopathy of prematurity by diode laser panretinal photocoagulation. Design Retrospective study. Participants Fifteen eyes in eight infants. Methods A review was carried out on infants between 23 and 25.6 weeks gestational age admitted to The Royal Brisbane and Women's Hospital neonatal intensive care unit between 1992 and 2009. Main Outcome Measures Success of treatment, visual and refractive outcomes. Results Five hundred fifty‐four infants were admitted to neonatal intensive care unit, 373 survived till screening, and 304 had retinopathy of prematurity. Sixty‐six infants required treatment, and eight of these had aggressive posterior retinopathy of prematurity (2.5% of all infants with retinopathy of prematurity). Mean gestational age was 24.2 weeks, mean birthweight was 634 g, and treatment occurred at mean 34.1 weeks post‐menstrual age. The mean total number of burns per eye was 2967. Five of 15 treated eyes required retreatment. Two patients subsequently died of unrelated causes. Regression occurred in 9 of 11 remaining eyes; one eye progressed to stage 4b and another to stage 5 retinopathy of prematurity. Vitrectomy was performed in two eyes. Five eyes had 6/12 vision, one had 3/60, and three had no perception of light. Of the remaining two eyes, one had good fixation and the other had poor fixation. Conclusions Despite good structural outcomes, visual outcomes for conventional laser treatment of aggressive posterior retinopathy of prematurity are poor.